Clustering strategies for energy harvesting wireless sensor networks - Hong, Lizhi. (2013)
Wireless sensor network is a network of sensor nodes that scans the physical condition of the environment and transmit data to the end user. This kind of network is widely used in military and environmental applications. It is useful for these networks to be placed in remote areas where it is unsuitable for human to be deployed. With its usefulness for information gathering purposes, more efforts were done to improve on the current networks. Most of the improvements were done on creating energy efficient routing protocols to improve the finite lifetime of a sensor node. With the emergence of energy harvesting sensor nodes, it seems that the lifetime of a sensor node does not become a major constraint in a sensor network. Without the constraint of a sensor node lifetime, other areas of the network can be optimized further. An area of interest would be to improve and optimize the network performance. This project studies on how energy harvesting sensor nodes and existing clustering routing protocols could work together and improve performance of a network.